Challenges of English Teaching in Engineering Courses - Edita Bekteshi; Melihate Shala; Brikena Xhaferi (Journal of Modern Research in English Language Studies)
The purpose of this experimental study was to investigate English teaching and its impact on students from the engineering faculty in bilingual CLIL (Content and Language Integrated Learning) application. It was conducted in a public Higher Education Institution (HEI) in Kosovo, at the Faculty of Mechanical Engineering and Computing in which data were collected from 180 students. There were 56 students involved in the experimental group, whereas the control groups comprised of 68 students following conventional Technical Drawing with Descriptive Geometry class in native /Albanian language, and 56 students followed conventional English for Specific Purposes (ESP) classes as the second control group. Two teachers, one in engineering field, and one ESP teacher were involved in this study throughout the semester, i.e. fifteen weeks. The study incorporated parallel teaching, the same content in two different languages in the experimental group: Albanian/native language by the engineering practitioner, and English by the ESP teacher. The results of three test terms for all the three groups were analyzed by applying SPSS statistical package, and revealed that the experimental group achieved higher success in learning. The study concluded that if there is no teacher available to offer CLIL to future engineers, then teaching engineering courses with the engineering practitioner can be conducted in parallel fashion with the ESP teacher, who can contribute to positive effect in terms of certain engineering subcategories and English professional vocabulary. As such, this study may be considered as a potential example in offering new professional engineering courses which include bilingual paired teaching, of English and a professional course.